The Performance of Geosynthetic Reinforcement Road Pavement Over Expansive Soil Subgrade - Hairulla, .; Harianto, Tri; Djamaluddin, Abdul Rahman; Arsyad, Ardy (Civil Engineering Journal, 2024)
One of the problems faced in infrastructure development, especially roads, is problematic soils, including expansive soils, which are distributed around 20% of national road construction in Indonesia. Geosynthetics are reinforcement materials that can be used to overcome problematic soils. The study aimed to determine the behavior of expansive soil with geosynthetic reinforcement against swelling potential and swelling pressure in the wetting cycle. The research utilized an experimental approach involving three test concepts. The first was a control test without reinforcement. The second included a combination of geogrid, geotextile, and geomembrane layers, while the third utilized an H2Rx reinforcement layer. Analysis was carried out on the development potential and pressure; the test was carried out for 57 days using displacement sensors and pressure sensors, and data recording was carried out every 5 seconds using a computer. The findings from the results of this study indicated that the presence of reinforcement using a geosynthetic reinforcement layer can overcome the behavior that occurs in expansive soils with swelling potential and swelling pressure. The novelty of this research is the inclusion of a geosynthetic reinforcement layer on expansive soil combined with a drainage layer in the pavement subgrade. Doi: 10.28991/CEJ-2024-010-12-020 Full Text: PDF